2015
DOI: 10.1128/jvi.01444-15
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of H7N9 Influenza Viruses with a Polymorphism at PB2 Residue 627 in Chickens and Ferrets

Abstract: Poultry exposure is a major risk factor for human H7N9 zoonotic infections, for which the mode of transmission remains unclear. We studied the transmission of genetically related poultry and human H7N9 influenza viruses differing by four amino acids, including the host determinant PB2 residue 627. A/Silkie chicken/HK/1772/2014 (SCk1772) and A/HK/3263/14 (HK3263) replicated to comparable titers in chickens, with superior oropharyngeal over cloacal shedding; both viruses transmitted efficiently among chickens vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…Mutations in the polymerase genes highlighted in Table 2 may have increased in frequency as a result of selection during circulation in poultry, but they appear to have minimal impact on virus replication and transmission in mammals. The limited transmissibility by respiratory droplets of second-and third-wave H7N9 viruses in ferrets tested here aligns with other studies which have reported transmission primarily among cohoused animals (52). Importantly, the similar transmission profile of H7N9 viruses between first-wave isolates and viruses isolated during the second and third waves suggest that vaccine and antiviral candidates which limit the transmissibility of the commonly employed Anhui/1/13 virus would maintain a comparable efficacy against more recently detected H7N9 viruses (53).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mutations in the polymerase genes highlighted in Table 2 may have increased in frequency as a result of selection during circulation in poultry, but they appear to have minimal impact on virus replication and transmission in mammals. The limited transmissibility by respiratory droplets of second-and third-wave H7N9 viruses in ferrets tested here aligns with other studies which have reported transmission primarily among cohoused animals (52). Importantly, the similar transmission profile of H7N9 viruses between first-wave isolates and viruses isolated during the second and third waves suggest that vaccine and antiviral candidates which limit the transmissibility of the commonly employed Anhui/1/13 virus would maintain a comparable efficacy against more recently detected H7N9 viruses (53).…”
Section: Discussionsupporting
confidence: 88%
“…While potential correlations between ocular tropism detected in the murine model and human susceptibility to influenza viruses following ocular exposure still are poorly understood, these data underscore the necessity of evaluating influenza viruses for the capacity to cause mammalian infection following alternate inoculation routes, even in the absence of a demonstrated tropism outside the respiratory tract. As observed in this study with shv/Egypt/07 virus, H7N9 viruses isolated from poultry from multiple waves have demonstrated reduced transmissibility in the ferret model compared with viruses isolated from humans (30,31,52). While this can be explained in part by sequence differences often present between poultry-and human-isolated viruses (notably at PB2 residue 627), further examination of how these viruses diverge will allow for a more precise understanding of the adaptation these viruses have undergone to cause human disease.…”
Section: Discussionsupporting
confidence: 60%
“…Guinea pigs and ferrets are two well-established animal models for the evaluation of transmissibility of influenza viruses (Gao et al 2009;Steel et al 2009;Herfst et al 2012;Imai et al 2012;Zhang et al 2013b). The H7N9 viruses, especially the human isolates, transmitted efficiently among guinea pigs or ferrets via direct contact (Belser et al 2013;Zhu et al 2013;Gabbard et al 2014;Luk et al 2015;Sun et al 2018). Compared with natural H5N1 viruses, which have never acquired respiratory droplet transmissibility, many studies have reported that both H7N9 LPAIV and HPAIV can transmit via respiratory droplets in guinea pigs and ferrets, although the efficiency of virus transmis- All six low pathogenic viruses and five of the six highly pathogenic viruses bound well to both human-type and avian-type receptors, whereas one of the six highly pathogenic viruses bound only to avian-type receptors.…”
Section: Transmissionmentioning
confidence: 99%
“…Other parameters than the duration or level of shedding influencing transmission efficacy include stability in the environment (in feces, water, dust or air) as well as the infectious dose necessary to infect a naïve animal. It would also be interesting to assess whether INDO AT6 could be better transmitted to mammals than INDO WT by performing chicken to ferret airborne transmission 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%